2015
DOI: 10.3390/md13031375
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Protects Steroidogenesis from Hydrogen Peroxide-Induced Oxidative Stress in Mouse Leydig Cells

Abstract: Androgens, especially testosterone produced in Leydig cells, play an essential role in development of the male reproductive phenotype and fertility. However, testicular oxidative stress may cause a decline in testosterone production. Many antioxidants have been used as reactive oxygen species (ROS) scavengers to eliminate oxidative stress to protect steroidogenesis. Astaxanthin (AST), a natural extract from algae and plants ubiquitous in the marine environment, has been shown to have antioxidant activity in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
(47 reference statements)
1
29
0
Order By: Relevance
“…In the present study, we determined that the optimal concentration of AST that has the best protective effect on ARPE-19 cells is 40 mg/L, being consistent with a previous study [18]. Here, we only studied its effect on this specific type of cells.…”
Section: Comparative Analysissupporting
confidence: 84%
“…In the present study, we determined that the optimal concentration of AST that has the best protective effect on ARPE-19 cells is 40 mg/L, being consistent with a previous study [18]. Here, we only studied its effect on this specific type of cells.…”
Section: Comparative Analysissupporting
confidence: 84%
“…508 By combining virtual-and structure-based ligand screening approaches, a database of >100 caulerpin analogues was efficiently evaluated in silico for potential inhibitory activity against monoamine oxidase B, 509 while astaxanthin and other algal carotenoids have been the focus of many studies and reviews. [510][511][512][513][514][515][516][517][518]…”
Section: Green Algaementioning
confidence: 99%
“…Elevated levels of ROS have been shown to be associated with several diseases, including neurodegenerative disease and cancer (3,4). Multiple studies have indicated that ROS inhibits testosterone production in Leydig cells by dissipating mitochondrial membrane potential, and reducing the expression and activity of testicular steroidogenic enzymes (5)(6)(7). Thus, the accumulation of ROS during the ageing process results in reduced levels of testosterone (8).…”
Section: Introductionmentioning
confidence: 99%